Design and evaluation of professional commitment development model in nursing students using structural equation modeling - Mandana Arash; Nadergholi Gourchian; Parivash Jafari; Akhtar Jamali (Zanjan University of Medical Sciences and Health Services, 2023)
Background & Objectives: Professional commitment plays an essential role in the improvement of the performance and professional behaviors of nurses and a major part of it is formed and developed during university education. In this regard, the present research aimed to design and evaluate the development model of professional commitment in nursing students. Materials & Methods: The present applied research was quantitative in terms of data type and descriptive in terms of survey-correlation type. The data were collected through a researcher-made questionnaire from 305 participants who were selected using a simple random method from nursing students of Islamic Azad University, Karaj Branch, Iran between 2020 and 2021. Data analysis was performed based on factor analysis and structural equation modeling in SPSS (version 26) and Smartpls 3 software. Results: Sampling adequacy and factors affecting the development of professional commitment were confirmed using exploratory factor analysis in the form of eight factors (individual, structural, socio-cultural, educational, managerial, economic, legal, and spiritual) and 60 components. Furthermore, the factor load of each factor was determined by confirmatory factor analysis. The final model designed by the structural equation method was evaluated as a very good model. Conclusion: There is a lack of an efficient nursing workforce and the development of professional commitment affects the desire of nurses to remain in their profession and provide quality and safe care. Therefore, it is necessary to consider the approved model resulting from this research as a valid framework in the policy-making of the nursing profession.